Community health officer: the concept of mid-level health care providers - Desai, Shrikant; Bishnoi, Ravin K.; Punjot, Pankaj (International Journal Of Community Medicine And Public Health, 2020)
The concept of mid-level health providers started 100 years ago in many countries and showed a remarkable change in their health indicators. Since last 10 years, the growth of health professionals is in rise with its new emerging roles. Special training with adopted skills is required for mid-level health care providers and the outline roles and responsibilities are already in existence for them. Mid-level health care providers are new emerging workforce in healthcare sector. India is alarming country for disease burden and to cover the huge gap in providing health care facilities, it requires the mid-level health care providers at different settings of the country. Indian community setting is in need to have access of affordable health care and government of India through National Health Mission (NHM) has declare the new pivotal role of community health officer (CHO) with its constructed roles and responsibilities for public health. According to NMC bill 2019, nurses are the first choice for CHO and this will also pave the way for professional development. Since there is global shortage of healthcare professionals and raising need of health care facilities especially in community setting, CHO is new evolving role which will promote the health care in access to community public. CHO being Midlevel health care provider will reduce the burden of other healthcare professionals and also contribute to achieve the aim of ‘health for all’. The aim of this review was to bring a new insight of CHO with its global concept.